Production and nitrogen uptake of grasses on different shading and fertilization - Sirait, J; Purwantari, N.D; Simanihuruk, K (Indonesian Journal of Animal and Veterinary Sciences, 2005)
An experiment was conducted in Indonesian Research Institute for Animal Production (IRIAP) Bogor, West Java. The objective of this research was to study the production and nitrogen uptake of three short grasses species for grazing namely Paspalum notatum, Brachiaria humidicola, Stenotaphrum secundatum on different shading and fertilization. This experiment was arranged in split-split plot design. The main plot was shading level (0, 38, and 56%); sub-plot was fertilizer dosage (0, 100, and 200 kg N/ha) while sub-sub plot was grass species. Data were analyzed by analysis of variance, and continued with Duncan multiple range test (DMRT) if there were significantly different among treatments. The highest shoot production, shoot/root ratio, and crude protein content were observed on S. secundatum with 38% shading levels and 100 kg N/ha fertilizer. The higher shading level had the lower nitrogen uptake by plant, whereas the higher fertilizer dosage gave higher nitrogen uptake. Â  Â  Key Words: Shading, Fertilization, Production, Nitrogen Uptake